Avaliação dos métodos de imersão, spray e dinâmico utilizados na fabricação de filmes nanoestruturados de nanofolhas de grafeno pela técnica de automontagem. - Mello, Waldomiro Luiz Rios de (Universidade Federal de São Carlos, 2014)
In this work we have compared the way graphene oxide nanoplatelets are nanostructured in bilayers of poly(diallyldimethylammonium chloride) (PDDA) and reduced graphene oxide stabilized in poly(sodium 4-styrenesulfonate) (GPSS), called as (PDDA-GPSS)n, with n representing the number of deposited bilayers. LbL (layer-by-layer) films were fabricated by the self-assembly technique throughout the dipping, spray and dynamic methodologies, available at Laboratory FINEP1, UFSCar, campus Sorocaba. When compared with other bottom-up strategies employed in the build-up of nanostructured ultrathin films, the LbL technique is simple, cheap and easy to handle, beside the incorporation of distinct materials in the film structure, not limited to the form and size of substrates. The times used for the polyelectrolytes in the dipping and dynamic methods were based on the kinetic growth of the (PDDA-GPSS)8 films. In the spray methodology the time used was based initially in the literature and further confirmed by experimental data considering pressure and spray time. All nanostructures formed were characterized by UV-vis spectroscopy, atomic force microscopy, scanning electron microscopy, profilometry and impedance spectroscopy. In all cases it was observed a linear growth of the LbL structures, pointing that the same amount of material was adsorbed at each deposition step. Films obtained from the dynamic methodology indicated higher amount of material adsorbed in the nanostructures, and by an adequate control of the parameters used in the self-assembly methods by physical adsorption one can make a fine tuning regarding to the spontaneous aggregation of the nanoplatelets at solid interfaces.
EVALUATION OF DIPPING, SPRAY AND DYNAMIC METHODS APPLIED ON NANOSTRUCTURED THIN FILMS OF GRAPHENE NANOPLATELETS BY THE SELF-ASSEMBLY TECHNIQUE.
Keywords: filmes finos; materiais nanoestruturados; filmes LbL; spray; imersão; LbL dinâmico; microcanal; nanofolhas de grafeno.; LbL Films; spray; dipping; dynamic LbL; graphene nanoplatelet; OUTROS